Identification of plant genetic resources affected by shrimp farming in the southwestern coastal region of Bangladesh - Ahmed, MB; Islam, MM; Islam, MM (International Journal of Agricultural Research, Innovation and Technology, 2022)
The main purpose of the study was to identify the plant genetic resources (PGRs) affected by shrimp farming and to determine their magnitude of vulnerability. Data were collected from randomly selected 100 respondents, through personal interview, using an interview schedule, at Dumuria upazila of Khulna district, during 16 November 2009 to 15 February 2010. The fruit PGRs were more affected by shrimp farming than that of timber yielding and other types of PGRs. Among the 18-fruit PGRs available, all were endangered, except indigenous velvet apple, Diospyros peregrine (Gaertn.) Gürke, which was in threatened condition. Among the fruit species, banana, Musa acuminate; guava, Psidium guajava L.; jackfruit, Artocarpus heterophyllus Lam.; sapota, Manilkara zapota L. and betel nut, Areca catechu L. were in highly endangered. Among the 17-timber yielding and other plant species, only 7-PGRs were affected by shrimp farming while majority (10-PGRs) had been available in different extents. Among the vulnerable PGRs, bamboo, Bambusa bambos (L.) Voss; flame of the forest, Delonix regia (Boj. ex Hook.) Raf.; teak, Tectona grandis L.f. and banyan, Ficus benghalensis L. were endangered, while Indian ash tree, Lannea coromandelica (Houtt.) Merr.; ipil-ipil, Leucaena leucocephala (Lam.) de Wit and cool mat, Schumannianthus dichotomus (Roxb.) Gagnep. were in threatened condition. In general, the total fruit trees decreased in numbers (-74.17%) after inception of shrimp farming. On the other hand, the total numbers of timber yielding plants increased by 15.45%. From the overall consideration (irrespective of types), the number of plant population decreased (-58.10%) after inception of shrimp farming. It means that the plant species were affected by shrimp farming and became endangered. Int. J. Agril. Res. Innov. Tech. 11(2): 18-26, Dec 2021